Faktor-Faktor yang Berhubungan dengan Motivasi Belajar Mahasiswa TK III Program D.III Keperawatan Akademi Keperawatan Royhan Tahun 2012 - Sariah Sariah (STIKes Persada Husada Indonesia, 2018)
Motivation is a moving spirit direction, and supporting human behaviors. Motivation is a mental encouragement which motivates and aims human behaviors includes learning behavior. Learning motivation is strongly related to the achievenment of education programs. thus the author thought that this condition needed to be researched. The purpose of this research was to find the factors which related with learning motivation of studens Grade III of Royhan Nursing Academy. This research was a cross-sectional reseach design using univariat, bivariate and multivariate analysis 70 subjects of grade III’s student of Royhan Nursing Academy. The research factors were internal factors such as ambition, interest, and hope meanwhile external factors were campus atmosphere academyc and non academyc and family support which were considered to have relation with students learning motivations. The findings skewed that the proportion of respondens learning motivation almost balance among them who have good and less learning motivation (51,4 % and 48,6 %). The variables which influenced to student learning motivation, all of the variables were related, except atmosphere of non academyc campus, with (p value = 0,240 . Family’s support was a dominant factor which related to student learning motivation. Hence, the researcher suggested to other practitioners to do the in depth research about students learning motivation of Royhan Nursing Academy with using a qualitative design, therefore it will explore more about the problems of learning motivation among student